Synthesis and Characterization of ZnO/Cellulose Acetate Composite and its Activity as Antibacterial Agent - Khefanny, Yemima Chellyne; Charlena; Sugiarti, Sri (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Cellulose is an abundant natural polymer that can be applied in various fields. Cellulose has many types and derivatives, one of which is cellulose acetate. Cellulose can be obtained from various natural sources such as kepok banana peel. The a-cellulose content in kepok banana peel is high enough at 94% so that it can be utilized as a cellulose acetate raw material. Modification of cellulose acetate using antibacterial agents is needed, considering that cellulose does not have antibacterial properties. Metal oxide materials such as ZnO nanoparticles are used as antibacterial agents. This study added ZnO nanoparticles to cellulose acetate and tested its antibacterial activity. The characteristics of ZnO were analyzed by UV-Vis, PSA, and FTIR. The characteristics of cellulose acetate and composites were analyzed by FTIR and XRD. Antibacterial activity tests were performed on all samples. The results showed the band gap value of ZnO was 3.37 eV. The average size of ZnO nanoparticle distribution using PSA was 96.23 nm with an average PI value of 0.151. An indicator that the ZnO compound and cellulose acetate have been sucessfully mixed is the absorption band at wave number 488 cm−1. A composite crystal size of 24.14 nm and a crystallinity percentage of 34.05% were found using XRD data. S. aureus bacteria are more inhibited by all evaluated substances antibacterial properties than E. coli germs. ZnO/Cellulose Acetate composite is categorized as strong inhibition, while ZnO nanoparticles are categorized as medium inhibition.